(untitled) (The Pakistan Development Review, 2013)
This paper is an attempt to understand the position of Indian women in the family and its influence on their migration decision. The migration-empowerment relation can be explained through relative measures like intra-household decision making indicators, and age and educational differences. The data for the purpose of the study has been drawn from the various rounds of NSSO and NFHS and it has been analysed at the state level due to data limitations for explanatory variables at the household level. The bi-variate findings show economic decision making related to large household purchases, decisions on mobility and spousal educational differences which exhibit a linear relation with the women’s migration decision. The empirical findings suggest the women’s greater involvement on own health care, spousal age and educational differences significantly influence their migration decision. This suggests that women’s empowerment influences their migration decision. JEL Classification: J10, J16 Keywords: Empowerment, Migration, Women, India, Relative Measures